Use of complementary alternative medicines in patients with gastrointestinal diseases - ISHII, Kunihide; SATA, Michio; FUKUSHIMA, Hirohumi; YANO, Yoichi; KUWAHARA, Reichiro; YAMASHITA, Fumihiko; HISAMOCHI, Akiko; SAKAI, Hironori; SHIRACHI, Miki; KUMASHIRO, Ryukichi; ONO, Noriyuki; MIYAJIMA, Ichiro; et al. (Kanzo, 2003)
We investigated the use of complementary alternative medicines (CAM) in patients with gastrointestinal diseases by inquiry sheet. A total of 451 answer sheets were recovered. More than 70% was or is taking CAM. Most of them began taking them without consulting doctors. Ten per cent of patients did not receive an appropriate direction from their doctors in consultation. In 3 patients (0.9%), biochemical tests was deteriorated. Twenty-nine patients (8.4%) took these items to compensate the drugs given by doctors. Proper handling and location of CAM, together with understanding of CAM by doctors are desirable.